KEKEBALAN KEDUTAAN BESAR DAN KONSULAT ASING DALAM PENYELESAIAN PERSELISIHAN PERBURUHAN - Revirta Arshinta Suharta; Abdul Maasba Magassing; Iin Karita Sakharina (Faculty of Law, Universitas Riau, 2018)
The purpose of this research is to understand employee’s rights especially Indonesian citizen who work as local staff at foreign embassy or consulate, also the existing of immunities of foreign embassy and consulate in labour disputes settlement. This research is used normative method with statute approach, conceptual approach and comparative approach. The results of this research are the rights of employee especially local staff are written under working agreements according to Indonesia labour law. The embassy legal standing as a party on the working agreement has fulfilled substantial element as a employer. Furthermore, related to application of immunity in labour disputes, Indonesia court decisions shown changes from absolute immunity to relative immunities.Keywords : Diplomatic Immunity, Embassy, Labour Dispute, Local Staff